Factors associated with long‐term outcomes in pediatric refractory status epilepticus. (12th July 2021) - Gaínza‐Lein, Marina; Barcia Aguilar, Cristina; Piantino, Juan; Chapman, Kevin E.; Sánchez Fernández, Iván; Amengual‐Gual, Marta; Anderson, Anne; Appavu, Brian; Arya, Ravindra; Brenton, James Nicholas; Carpenter, Jessica L.; Clark, Justice; et al.
Abstract: Objective: This study was undertaken to describe long‐term clinical and developmental outcomes in pediatric refractory status epilepticus (RSE) and identify factors associated with new neurological deficits after RSE. Methods: We performed retrospective analyses of prospectively collected observational data from June 2011 to March 2020 on pediatric patients with RSE. We analyzed clinical outcomes from at least 30 days after RSE and, in a subanalysis, we assessed developmental outcomes and evaluated risk factors in previously normally developed patients. Results: Follow‐up data on outcomes were available in 276 patients (56.5% males). The median (interquartile range [IQR]) follow‐up duration was 1.6 (.9–2.7) years. The in‐hospital mortality rate was 4% (16/403 patients), and 15 (5.4%) patients had died after hospital discharge. One hundred sixty‐six (62.9%) patients had subsequent unprovoked seizures, and 44 (16.9%) patients had a repeated RSE episode. Among 116 patients with normal development before RSE, 42 of 107 (39.3%) patients with available data had new neurological deficits (cognitive, behavioral, or motor). Patients with new deficits had longer median (IQR) electroclinical RSE duration than patients without new deficits (10.3 [2.1–134.5] h vs. 4 [1.6–16] h, p = .011, adjusted odds ratio = 1.003, 95% confidence interval = 1.0008–1.0069, p = .027). The proportion of patients with an unfavorable functional outcome (Glasgow Outcome Scale‐Extended score ≥ 4) was 22 of 90 (24.4%), and they were more likely to have received a continuous infusion. Significance: About one third of patients without prior epilepsy developed recurrent unprovoked seizures after the RSE episode. In previously normally developing patients, 39% presented with new deficits during follow‐up, with longer electroclinical RSE duration as a predictor.